Relationship between relative age measured through decimal age, physical variables and anthropometry in elite youth soccer players - Asín-Izquierdo, I.; Chena, M.; de Dios-Álvarez, V.; Galiano, C. (The Physician and Sportsmedicine, 2024)
Introduction Age differences between athletes born in the same year, as well as an over-representation of older players, are known as the Relative Age Effect (RAE). Players born at the beginning of the selection year have a physical and anthropometric advantage over their younger peers. Experts keep looking for new prediction variables for talent identification.